INSULYSIN INHIBITORS AS NOVEL ANTI-DIABETIC AGENTS: FROM COMPUTATIONAL DESIGN TO PRE-CLINICAL VALIDATION - Divanshi Suryavanshi; Dr.Pragnesh Patani; Milan Jadav; Dr. Nishkruti R. Mehta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Diabetes mellitus is a health crisis that has been increasing worldwide in prevalence and has fewer treatment options. The enzyme insulysin (also called insulin-degrading enzyme, IDE) is also important in insulin metabolism and glucose homeostasis. New insulysin inhibitors are coming up as effective therapeutic agents in the management of diabetes. Objective: This review assesses the potential to use novel insulinase inhibitors as anti-diabetic agents using an integrated approach involving computational and experimental methods in streptozotocin-nicotinamide induced diabetic rat models. Methods: An extensive literature review was done with the help of such databases as PubMed, Scopus, and Web of Science that included publications dated 2015-2024. Inlay terms were insulin degrading enzyme, insulin-degrading enzyme, in-silico and STZ-NAD diabetic model. Results: The existing data indicates that insulinase inhibitors show great anti-diabetic effects in a variety of mechanisms such as the increased insulin sensitivity, improved β-cell act, and decreased insulin degradation. In-silico research indicates potential binding affinities and pharmacokinetic characteristics whereas in-vivo research in STZ-NAD models demonstrates better glycemic control and morphology of the pancreas. Conclusion: Novel insulinase inhibitors offer a perspective in treating diabetes and a combination of in- Silico and in-vivo studies offers a great strength to the clinical efficacy of the compound.